2015
DOI: 10.1002/nbm.3350
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI analysis for the evaluation of MR‐guided high intensity focused ultrasound tumor treatment

Abstract: Nicolay, K. (2015). Multiparametric MRI analysis for the evaluation of MR-guided high intensity focused ultrasound tumor treatment. NMR in Biomedicine, 28(9), 1125-1140. DOI: 10.1002/nbm.3350 General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
2
12
0
1
Order By: Relevance
“…It is important to note that in this study neither tumor volume nor water ADC predicted effective ablation. Similar to prior publications, we observed an early non‐significant decrease in ADC, and a trend towards increasing water ADC over time in the ablated region . Additionally, at 5 d after treatment the ADC was higher in the ablated zone than in the partially treated zone, consistent with the literature .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is important to note that in this study neither tumor volume nor water ADC predicted effective ablation. Similar to prior publications, we observed an early non‐significant decrease in ADC, and a trend towards increasing water ADC over time in the ablated region . Additionally, at 5 d after treatment the ADC was higher in the ablated zone than in the partially treated zone, consistent with the literature .…”
Section: Discussionsupporting
confidence: 91%
“…The early reduction in HP 13 C urea and its relationship to increased tumor hypoxia is consistent with a prior study, which reported that reduced 13 C urea AUC was associated with increased hypoxia in high‐ versus low‐grade TRAMP tumors . The clinical gold standard for measuring effective HIFU is DCE MRI, and the observed decrease in K trans and DCE MRI AUC immediately after HIFU and its recovery days after treatment have repeatedly been demonstrated in other studies . However, it is important to note that, if follow‐up HIFU is required to treat residual tumor after the initial DCE MRI, entrapped contrast agent within coagulated tissue regions could negatively impact the accuracy of the proton resonance frequency shift MR thermometry .…”
Section: Discussionsupporting
confidence: 87%
“…Cell lysis that is associated with necrosis generally leads to elevated tissue ADC values . Indeed, a strongly significant ( P < 0.001) ADC increase has been observed at 1 week after HIFU treatment of human liver tumors and at 3 days after treatment of mouse and rat subcutaneous tumors. In the latter study, in which we treated the rat tumors in a clinical 3Tesla (T) MR‐guided HIFU system, an average ADC increase of 0.51 × 10 −3 mm 2 /s was observed at 3 days after therapy.…”
Section: Mri‐detectable Hifu Treatment Effectsmentioning
confidence: 98%
“…In a later study, we have performed multiparametric MRI consisting of T 1 , T 2 , ADC, APT‐weighted signal, and T 1ρ mapping to evaluate MR‐guided HIFU treatment of rat tumors in a clinical 3T MR‐HIFU system. The cluster analysis showed that the extent of nonviable tumor tissue could be accurately determined at 3 days after HIFU treatment when the ADC and APT‐weighted signal data were combined .…”
Section: Mri‐detectable Hifu Treatment Effectsmentioning
confidence: 99%
“…40 Protein denaturation, a cause of thermally induced cell death, has been detected using magnetization transfer, amide proton transfer, and T 1 q techniques. 15,18,19 Irreversible protein damage also causes increased tissue stiffness detectable using MR elastography, 16 but sublethal heating has a contradictory effect, and the method depends on the ability to apply imaging-synchronized mechanical waves to the tissue of interest. Finally, when a time series of MR temperature maps is available, the delivered thermal dose can be calculated.…”
Section: Discussionmentioning
confidence: 99%